Simulation of Automatic Solar Tracker Control System Using Proteus Application - Efendi, Erwan Tri; Wibowo, Bayu Setyo; Dhiyaussalam, Dhiyaussalam; Wardhany, Arum Kusuma; Wibisono , Arifin (Politeknik Negeri Semarang, 2024)
As a tropical country, Indonesia possesses significant renewable energy potential, particularly from solar and wind sources. However, seasonal variations—such as high solar intensity during the dry season and increased wind speeds during the rainy season—pose challenges to optimizing solar cell utilization. While solar energy presents an ideal solution for clean energy transition, static photovoltaic (PV) systems suffer from efficiency limitations due to their inability to track the sun’s movement. Dual-axis solar trackers can enhance energy efficiency by 25–35% compared to fixed systems, particularly in tropical regions with dynamic solar positioning. However, large-scale physical implementation requires substantial investment, making simulation tools like Proteus essential for computational validation prior to real-world deployment. Proteus facilitates comprehensive modeling of LDR sensors, servo motors, and microcontroller-based control algorithms (e.g., Arduino) in a precise virtual environment. This approach also evaluates the impact of tropical conditions (e.g., humidity, rainfall) on system reliability while optimizing designs to reduce costs. Integrating current research with Proteus simulations offers a robust methodology to accelerate solar tracker adoption in Indonesia.